The causality between intestinal flora and allergic diseases: Insights from a bi-directional two-sample Mendelian randomization analysis - Jin, Qiubai; Ren, Feihong; Dai, Dan; Sun, Nan; Qian, Yiyun; Song, Ping (Frontiers in Immunology, 2023)
Abstract Background: Growing evidence shows a significant association between intestinal flora and allergic diseases, specifically atopic dermatitis (AD), allergic rhinitis (AR), and allergic asthma (AA). But their causality has not been clarified. Objective: To study the causality between intestinal flora classification and AD, AR, or AA, we conducted a bidirectional two-sample Mendelian randomization (MR) analysis. Materials and Methods: We obtained the summary data of intestinal flora, AD, AR, and AA from the published genome-wide association study (GWAS). Inverse-variance weighted (IVW) method is the primary method to analyze causality in MR analysis. Several sensitivity analyses were carried out to verify the robustness of MR results. Reverse MR analysis is also performed to assess whether there is a reverse causality. Results: A total of 7 bacterial taxa associated with AD, AR, and AA were identified by the current TSMR analysis. Specifically, the genus Dialister（P=0.034）and genus Prevotella（P=0.047）were associated with a higher risk of AD, whereas class Coriobacteriia (P=0.034) and its child taxon, order Coriobacteriales (P=0.034) and family Coriobacteriaceae (P=0.034), all had a protective effect on AR. In addition, the family Victivallaceae (P=0.019) was identified as a risk factor for AR. We also noticed a positive association between the genus Holdemanella (P=0.046) and AA. The reverse MR analysis didn’t suggest any evidence of reverse causality from allergic diseases to the intestinal flora. Conclusion: We confirmed the causal relationship between intestinal flora and allergic diseases and provided an innovative perspective for the research of allergic diseases: targeted regulation of dysregulation of specific bacterial taxa to prevent and treat AD, AR, and AA.